Res judicata and consumer protection in the EU: the dialogue between the Courts (and the legislator) - Marco Morotti (Revista Ítalo-Española de Derecho Procesal, 2024)
The case law of the European Court of Justice (CJEU), despite confirming in theory the importance of res judicata, has regularly affirmed the need to overcome stability of national judges’ opinions formally qualified as final if that is needed to ensure effective consumers protection. Against this scenario, the Italian Supreme Court (Cass., sez. un. 6 April 2023, n. 9479), seems to have initiated a dialogue with the CJEU, mainly aimed at giving actuation of the principles enacted by the European Court but nevertheless with some apparent revindications of autonomy. The variety of solutions adopted by national judges and the creative effort of the Italian Supreme Court seem to confirm that an intervention by European or national legislators could be required at this point on the matter.